Structuring a Pharmaceutical Parent Company Organization: A Value-Based Approach, The Case of TPICO: Structuring a pharmaceutical parent company organization - Sanaz Peyrovan; Mehdi Mohammadzadeh; Mohammad Reza Saeedi; Hossein Dadfar (Iranian Journal of Pharmaceutical Sciences, 2012)
Todays, the parent company has a great role in managing and monitoring subsidiaries and companies in promoting their industrial activities. But, the main problem for pharmaceutical parent companies is the lack of clarity and confusion of responsibilities between units. Successful parenting needs to create the element of ’fit’ between the ways parent operates – parent characteristics – and its business characteristics. However, the main parent characteristic is the parent structure, and restructuring is the main challenge in unstable pharmaceutical market. In fact, the parent strategy should determine how value can be added to every organizational structure and parent structure should be proportionate to its dominant value creation strategy. The value drivers are very different in pharmaceutical industry regarding the fast changing technology. The aim of this study is to explore an appropriate valuecreating structure for the largest pharmaceutical parent company in Iran, Tamin Pharmaceutical Investment Company (TPICO). This study concentrates on the sources of value in this special domain and restructuring the parent company by considering the dominant value-creating strategy and pharmaceutical value drivers.